Evaluation of Public Response to e-PR Implementation by PT KAI: A Case Study of Service Satisfaction and Effectiveness - Lisdiantini, Netty; Azis, Aminudin; Subiyantoro, Subiyantoro; Surya Pratama, Hudha (PT. Banjarese Pacific Indonesia, 2024)
This research aims to evaluate the public response to the implementation of the e-PR service by PT. KAI, focusing on service satisfaction and effectiveness. In the context of public service digitalization, PT. KAI has taken an innovative step by introducing e-PR, an electronic public relations platform, to enhance engagement and communication with the public. Through online surveys , this study will collect user perception data related to the quality, accessibility, and benefits of the e-PR service. Data analysis will be conducted using descriptive and inferential statistical techniques to identify levels of satisfaction and factors influencing the effectiveness of e-PR. The results of this study are expected to provide valuable insights for PT. KAI in refining its digital communication strategy and improving service quality to the public. Thus, this research is not only relevant to PT. KAI but also to digital PR practices in other industries